Incorporation of silica into the goethite structure: a microscopic and spectroscopic study - Ali, A.M. (Science Press, 2018)
Quartz and iron (hydr)oxide are reactive surface phases that are often associated with one another in soils and sediments. Despite the several studies on the coating of quartz with iron oxides, the reactivity of dissolved species (Si) leached from quartz with iron (hydr)oxides has received limited attention. In this study, goethite synthesized on quartz substrates were characterized using field emission scanning electron microscopy, X-ray diffraction (XRD), transmission electron microscopy, and Fourier-transform infrared (FT-IR) spectroscopy. The SEM characterization revealed that bundles of thin parallel aligned goethite rods were formed at pH > 10, while large pseudohexagonal crystals of twinned goethite needles were synthesized at pH â¤ 10 after dehydration and hydration in the alkaline media. TEM analysis showed expanded and distorted lattice spacing of the crystal structure of iron (hydr)oxide due to silica incorporation. The characterization showed that silica increased the crystallite size of the goethite and transformed its acicular texture to a larger, twinned needle structure. FT-IR and XRD analyses revealed band shifts in crystal bonds as well as new bond formations, which indicate the presence of changes in the chemical environment of FeâO and SiâO bonds. Thus, the presence of sorbed silicates modifies the crystal and lattice structure of goethite. Â© 2018 Science Press, Institute of Geochemistry, CAS and Springer-Verlag GmbH Germany, part of Springer Nature